Left atrial strain improves echocardiographic classification of diastolic function in patients with metabolic syndrome and overweight-obesity. (1st February 2022) - Alonso Gómez, Angel M.; Sierra, Lucas Tojal; Mora, Noris Mora; Toledo, Estefanía; Alonso, Alvaro; Uriarte, María Garrido; Sanchez, Carolina Sorto; Portillo, María P.; Rodriguez, Luis López; Arellano, Elena Escribano; Schröder, Helmut; Salas-Salvadó, Jordi
Abstract: Background: Current recommendations for echocardiographic assessment of diastolic function (2016 guidelines of the American Society of Echocardiography (ASE)/European Association of Cardiovascular Imaging (EACVI) in patients with metabolic syndrome and overweight/obesity result in a significant number of patients with indeterminate diastolic dysfunction (LVDD). The aim of this article is to study whether the use of the left atrial strain criterion (LALS) reduces the number of indeterminate patients. Methods: 229 patients were studied with a complete echocardiographic study that included left ventricular longitudinal strain (LVLS) analysis, LALS and a maximal ergospirometry test with assessment of oxygen uptake (VO2max ). Results: The mean age was 65 ± 5 years, 153 (67%) males, with a mean EF of 60 ± 5%. The mean LVLS was −19.4 ± 2% and the LALS Reservoir was 23.8 ± 7%. There were 140 patients who did not meet LVDD criteria and 82 who did meet the indeterminate LVDD criterion. When the left atrial volume index (LAVI) >34 ml/m 2 criterion was replaced in the 2016 ASE/EACVI algorithm by LALS Reservoir ≤20%, the number of indeterminate patients was reduced from 36% to 23% ( p  < 0.001) at the expense of increasing normal studies (61% and 74%). Adding the LALS Reservoir criterion ≤23% in the 82 patients of the indeterminate group resulted in two groups with a different VO2max (11.6 ± 3 and 18 ± 5 ml/kg/min, p:0.081). Conclusions: This study confirms the low prevalence of diastolic dysfunction in overweight/obese patients with metabolic syndrome. Adding left atrial strain criterion to the current recommendations significantly reduces the number of indeterminate patients by reclassifying them as normal. Highlights: Diastolic dysfunction is often associated with metabolic syndrome and overweight/obesity. Guidelines for echocardiographic diagnosis of diastolic dysfunction show a high proportion of indeterminate studies. It explores the usefulness of longitudinal left atrial strain for echocardiographic assessment of diastolic function. The use of this parameter reduces the number of indeterminate patients when applying current recommendations.